Comparing an Emergency Department–specific Antibiogram Versus Hospital-wide Antibiogram and Therapeutic Dilemmas for Uncomplicated Cystitis. Issue 3 (May 2019) - Peyko, Vincent; Daves, Alexander; Eggleston, Matthew
Abstract : Background: The emergency department (ED) lies between the inpatient and outpatient worlds. Varying rates of antimicrobial resistance along with the volume of patients presenting to the ED with potential urinary tract infections make empiric antibiotic selection difficult but vital. However, simply referring to the guidelines may neither optimize therapy nor mitigate resistance. Methods: This was a retrospective cohort study comparing antimicrobial sensitivities of women from home, diagnosed with uncomplicated cystitis and discharged home, versus sensitivities of an institution-wide antibiogram between September 1, 2016, and February 28, 2017. The primary outcome was determining whether there was a difference between Escherichia coli sensitivities in nonpregnant women older than 14 years, from home, being discharged home and diagnosed with uncomplicated cystitis versus an institution-specific antibiogram. Results: Over the study period, 258 patients were evaluated for uncomplicated cystitis with 128 patients included in the final analysis as the retrospective cohort after 130 patients were excluded. Statistically significant differences between the retrospective cohort and institution-wide antibiogram were 80.5% versus 57% ( P < 0.001) for amoxicillin/clavulanic acid, 85.9% versus 75% ( P = 0.007) for cefazolin, 94.5% versus 86% ( P = 0.008) for ceftriaxone, 96.1% versus 87% ( P = 0.003) for cefepime, 97.5% versus 66% ( P < 0.001) for levofloxacin, and 99.2% versus 95% ( P = 0.032) for nitrofurantoin, respectively. Conclusions: Our study shows differences between an ED-specific antibiogram and institution-wide antibiogram. Many common and guideline-recommended antimicrobials used to treat acute uncomplicated cystitis may not be appropriate. Compiling ED-specific antibiograms at all institutions may help to optimally guide therapy.